Pengembangan Instrument Tes Berpikir Kritis Gen-Z Dalam Materi Manusia dan Cinta - Subandri Simbolon; Hugo Theo Kurniason; Tetty Novitasari Simbolon (Jayapangus Press, 2021)
A close correlation between gadgets and the internet makes it easier for Gen-Z to access information but tends to be low in critical thinking. Regrettably, the must-needed critical thinking process in absorbing information is usually missed as the process of copying or imitating all the information is way much easier to do. This research aims to develop a test instrument that can measure the critical thinking quality of Gen-Z (students at the Pontianak State Catholic High School). The test instrument developed focuses on the topic of humans and love, one of the materials contained in regional culture and multicultural subjects offered in the first semester. The test instrument developed using formative research can measure the quality of students' critical thinking. In addition, the test instrument has a value of validity, reliability, index of difficulty, and distinguishing power as determined.